Choice of adjuvant and antigen composition alters the immunogenic profile of a SARS-CoV-2 subunit vaccine - Lykins, William R.; Pollet, Jeroen; White, Jessica A.; Keegan, Brian; Versteeg, Leroy; Strych, Ulrich; Chen, Wen-Hsiang; Mohamath, Raodoh; Ramer-Denisoff, Gabi; Reed, Sierra; Beaver, Samuel; Gerhardt, Alana; et al. (Frontiers in Drug Delivery, 2024)
Since their introduction, adjuvanted recombinant subunit vaccines against COVID-19 have played a pivotal role in protecting global populations. Optimizing the immune response's quality, amplitude, and durability to these vaccines depends on the appropriate adjuvant choice and dose in combination with the selected antigen. Here, we employed a preclinical mouse model to study the adaptive humoral and cellular immune responses to a SARS-CoV-2 receptor binding domain (RBD) antigen formulated with one of four different immune agonists (GLA, 3M-052, CpG 1826 [CpG], and dmLT), in combination with one of two different immune-stimulating formulations, a stabilized squalene emulsion (SE) or aluminum hydroxide (Alum). Using a weighted desirability index, we established an immunogenicity ranking for each adjuvant in combination with the RBD antigen. We found that formulations of the RBD with Alum in combination with either 3M-052 or CpG led to at least a 2-log increase in serum IgG production and a 1.3-to 2.2-log increase in the number of bone marrow-derived antibody-secreting cells compared to the RBD formulated with Alum without an additional agonist. In contrast, the RBD formulated with SE in combination with 3M-052 or CpG did not elicit an IgG response greater than the unadjuvanted control. Additionally, RBD formulated with 3M-052 or CpG on Alum generated a 0.8-or 1.6-log lower splenocyte IL-5 response (a pro-Th2 marker), respectively, than Alum without an additional agonist. When formulated with 3M-052-Alum, a bivalent vaccine containing the original lineage (Wuhan-Hu-1) and the Delta variant (B.1.617.2) RBD antigens led to a more than 2-log increase in neutralizing antibodies against an Omicron variant (B.1.1.529) pseudovirus in vaccinated animals compared to animals that received the monovalent RBD antigen. Our results suggest that optimal immune